The cowboy who saved Christmas - Thomas, Jodi; Lovelace, Sharla; Dunn, Scarlett (Kensington Books, 2020)
Father Goose: Dispirited by war, when Trapper Morgan accepts a job hauling five little rich girls to Dallas, all he cares about is the money. He doesn't expect they'll awaken his spirit--or that their intriguing nursemaid, Carolina, will awaken his heart. And when danger strikes as Christmas Eve nears, he definitely doesn't expect Carolina and the girls to risk their lives--for him . . .